(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
In this article are shown the results of researches of development of effective composite chemical reagents based on organic and inorganic ingredients for drilling fluids, used for the drilling of oil wells. In this article well give comparative properties of local drilling fluids compared with drilling fluids used in Russia, USA.